Understanding the WTO (WTO GenevaCH, 2004)
Provides information on the history of the WTO, the agreements. dispute settlement, new issues the Doha Agenda, the way the WTO deals with the special needs of developing countries, and the organization.
Additional copy located in the Office of the Secretary-General